Penerapan Model Pembelajaran Inkuri untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam (Penelitian Tindakan Kelas di Kelas VII SMP PKP JIS DKI Jakarta) - Sutiono; Marliza Oktapiani; Syarifah Soraya (LP. Ma'arif Janggan Magetan, 2023)
The fact shows that student achievement in Islamic religious education subjects is still low, the average student score is 6.4 while the class average is 6.7. The achievement figures for student learning outcomes have been going on for the last three (3) years. Facing this fact, researchers feel it is important to make maximum efforts in order to improve the quality of the learning process of Islamic religious education as indicated by maximum achievement figures. The research method used in this paper is descriptive method with experimental class action. Based on the application of the inquiry learning model in improving learning outcomes in Islamic religious education, it turns out to be able to change student learning outcomes in class VII SMP PKP JIS Jakarta. It appears that the average score of students' Islamic religious education learning outcomes in the pre-cycle is 51.6, this figure is far from ideal. After participating in cycle I there was an increase, which was 66.3, this figure was still not in the ideal category. As for after participating in cycle II, the average score of students' Islamic religious education learning outcomes was 82.8, this figure indicates the ideal category. thus applying the inquiry learning model, the learning process appears to be more meaningful and takes place effectively and efficiently enough to provide a stimulus for the involvement of all potential students, both cognitive and affective and psychomotor in carrying out Islamic religious education learning activities.